Penyuluhan Tentang Kesehatan Reproduksi Pada Remaja Putri Di Kota Palembang - Arie Anggraini; Wahyu Ernawati (JURNAL PENGABDIAN KADER BANGSA, 2026)
Adolescence is a transition period from childhood to adulthood, during this period many changes occur from biological, psychological, intellectual and economic changes. [1]. Based on data from the World Health Organization (WHO), as many as 33% of women experience reproductive health problems with poor conditions [3]. Meanwhile, based on data from the Global School Health Survey (GSHS), it states that around 3.3% of adolescents aged 15 to 19 years are diagnosed with AIDS, and there are only around 9.9% of adolescents aged 15-19 years who know about HIV/AIDS, as many as 0.7% of women and 4.5% of men stated that they had had sexual relations (Free Sex) [4]. The method used in this activity is counseling with lectures, and media slide presentations, leaflets, and flip charts. The target of this counseling is adolescent girls. This activity is measured by pretest evaluation, posttest with 15 questions to participants about reproductive health, reproductive health disorders and prevention of reproductive health disorders. The activity went well and had minimal obstacles. Reproductive health education for adolescent girls increased participants' knowledge by an average of 36.8 points. Fifty-three participants (88.3%) experienced a score increase of ≥ 36, while only seven (11.7%) experienced a score increase of ≤ 36.